2017
DOI: 10.1177/0146167217695554
|View full text |Cite
|
Sign up to set email alerts
|

When Silence Is Not Golden: Why Acknowledgment Matters Even When Being Excluded

Abstract: Following ostracism, individuals are highly sensitive to social cues. Here we investigate whether and when minimal acknowledgment can improve need satisfaction following an ostracism experience. In four studies, participants were either ostracized during Cyberball (Studies 1 and 2) or through a novel apartment-application paradigm (Studies 3 and 4). To signal acknowledgment following ostracism, participants were either thrown a ball a few times at the end of the Cyberball game, or received a message that was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 42 publications
(50 reference statements)
0
41
1
3
Order By: Relevance
“…It was surprising that seeing direct gaze did not alleviate the effects of exclusion in the present study, as previous research has demonstrated that even minimal acknowledgment can facilitate recovery after exclusion (Rudert et al, 2017). However, there is one important distinction between the current study and previous research examining how acknowledgment or inclusion moderates the effects of exclusion (Gross, 2009;Rudert et al, 2017;Twenge et al, 2007;Zwolinski, 2014).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…It was surprising that seeing direct gaze did not alleviate the effects of exclusion in the present study, as previous research has demonstrated that even minimal acknowledgment can facilitate recovery after exclusion (Rudert et al, 2017). However, there is one important distinction between the current study and previous research examining how acknowledgment or inclusion moderates the effects of exclusion (Gross, 2009;Rudert et al, 2017;Twenge et al, 2007;Zwolinski, 2014).…”
Section: Discussioncontrasting
confidence: 82%
“…On the other hand, recent research indicates that even negative feedback can alleviate distress caused by social exclusion (Rudert, Hales, Greifeneder, & Williams, 2017). An excluded individual may prefer even negative attention to being ignored altogether (see also O'Reilly, Robinson, Berdahl, & Banki, 2014).…”
mentioning
confidence: 99%
“…Due to the physical co-presence, the targets of social exclusion are highly aware that their inclusionary status is threatened. This might explain why their sensitivity towards social attention is so intense that any form of attention-even negative in tone-can satisfy their fundamental needs for belonging, self-esteem, meaningful existence, and control (i.e., minimal acknowledgement hypothesis; Rudert et al, 2017). In contrast, social exclusion episodes that occur in CMC environments are communicated through fewer sensory channels: In the Ostracism Online Tool used within this study, threats to individuals'…”
Section: Discussionmentioning
confidence: 99%
“…Although little research compared the effects of being ostracized and being rejected directly, experimental evidence showed that targets of ostracism reported a stronger threat of all four needs than targets of rejection (Zadro et al, 2005). This can be explained using the minimal acknowledgement hypothesis which postulates that individuals' fundamental needs are highly reactive to any kind of acknowledgement-even negative in tone-as it implies that one's existence is recognized by others (Rudert, Hales, Greifeneder, & Williams, 2017 (Zadro et al, 2005). Likewise, following the responsive theory of social exclusion (Freedman, Williams, & Beer, 2016), individuals' emotional reactions to social exclusion highly depend on whether the sources of exclusion are responsive towards them or not.…”
Section: H1mentioning
confidence: 99%
“…Understanding observers’ side‐taking is critical, since plenty of research has shown that ostracism is highly painful and threatening for its targets (for an overview, see Blackhart, Nelson, Knowles, & Baumeister, ; Hartgerink, van Beest, Wicherts, & Williams, ; Williams, ). Far less work has focused on the role of observers, who have the potential to make a difference by providing support and acknowledgement for ostracized targets, be it in an educational context, at work, or at home (Rudert & Greifeneder, ; Rudert, Hales, Greifeneder, & Williams, ). Yet, observers will not always side with the target and under certain conditions they may even join in ostracizing the target (Rudert, Reutner, Greifeneder, & Walker, ; Wesselmann, Wirth, Pryor, Reeder, & Williams, ; Wesselmann, Wirth, et al., ).…”
Section: Introductionmentioning
confidence: 99%